PENERAPAN MODEL PEMBELAJARAN GUIDED INQUIRY BASED VIDEO UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATERI ENERGI - Siti Maimuna; Mohammad Zaky Tatsar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students’ understanding of renewable energy concepts is often limited due to the abstract nature of the topic and the use of conventional instructional methods. This study aims to evaluate the effect of implementing a guided inquiry-based video learning model on the conceptual understanding of renewable energy among Grade X students. The research employed a quasi-experimental method with a one-group pretest-posttest design. The participants were Grade X students at MA Putri Al-Islahiyyah Tumpuk, Sambisirah Wonorejo Pasuruan. Instruments included lesson implementation observation sheets, pretest and posttest items, and student response questionnaires. Data were analyzed using validity and reliability testing, normality and homogeneity tests, and hypothesis testing through statistical analysis. The findings reveal a significant improvement in conceptual understanding following the implementation of the guided inquiry video-based learning model. Posttest scores were substantially higher than pretest scores, with t-test results indicating significance at the 5% level. This learning model was found to be effective and feasible, offering ease of use, affordability, and meaningful contributions in visualizing abstract concepts and fostering active student engagement. The study recommends the integration of video media and guided inquiry approaches in physics education curricula to support meaningful and innovative learning experiences